(untitled) (World Bulletin of Public Health, 2024)
Researchers have emphasized the close interrelationship of factors that determine the occurrence and development of mental illness for persons with comorbid forms of drug-related disorders. Meanwhile, the combination of alcohol addiction with schizophrenia contributes to an increase in the number of socially dangerous actions.